h - Kwon, Taekyoung; Lee, Mun-Kyu.; Kwon, Daesung; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 15th International Conference on Information Security and Cryptology, ICISC 2012, held in Seoul, Korea, in November 2012. The 32 revised full papers presented together with 3 invited talks were carefully selected from 120 submissions during two rounds of reviewing. The papers provide the latest results in research, development, and applications in the field of information security and cryptology. They are organized in topical sections on attack and defense, software and Web security, cryptanalysis, cryptographic protocol, identity-based encryption, efficient implementation, cloud computing security, side channel analysis, digital signature, and privacy enhancement.
Attack and defense -- Software and Web security -- Cryptanalysis -- Cryptographic protocol -- Identity-based encryption -- Efficient implementation -- Cloud computing security -- Side channel analysis -- Digital signature -- Privacy enhancement.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems